Multiphotoluminescence from a Triphenylamine Derivative and Its Application in White Organic Light‐Emitting Diodes Based on a Single Emissive Layer. Issue 23 (16th April 2019) - Li, Xiaomeng; Cui, Jieshun; Ba, Qiankai; Zhang, Zhe; Chen, Shaoqing; Yin, Guoxin; Wang, Yu; Li, Bobo; Xiang, Guohong; Kim, Kwang Soo; Xu, Hu; Zhang, Zhaoyu; et al.
Abstract: White organic light‐emitting diode (WOLED) technology has attracted considerable attention because of its potential use as a next‐generation solid‐state lighting source. However, most of the reported WOLEDs that employ the combination of multi‐emissive materials to generate white emission may suffer from color instability, high material cost, and a complex fabrication procedure which can be diminished by the single‐emitter‐based WOLED. Herein, a color‐tunable material, tris(4‐(phenylethynyl)phenyl)amine (TPEPA), is reported, whose photoluminescence (PL) spectrum is altered by adjusting the thermal annealing temperature nearly encompassing the entire visible spectra. Density functional theory calculations and transmission electron microscopy results offer mechanistic understanding of the PL redshift resulting from thermally activated rotation of benzene rings and rotation of 4‐(phenylethynyl) phenyl)amine connected to the central nitrogen atom that lead to formation of ordered molecular packing which improves the π–π stacking degree and increases electronic coupling. Further, by precisely controlling the annealing time and temperature, a white‐light OLED is fabricated with the maximum external quantum efficiency of 3.4% with TPEPA as the only emissive molecule. As far as it is known, thus far, this is the best performance achieved for single small organic molecule based WOLED devices. Abstract : Single‐emissive‐layer white organic light‐emitting diodes (WOLEDs) are demonstrated by using a small molecule, tris(4‐(phenylethynyl)phenyl)amine, without additional doping. By adjusting the annealing temperature, multiphotoluminescence is observed and various energy states are formed due to the change in the molecular configuration and packing with smaller spacing from heat‐induced rotation of the benzene rings.